PECULIARITIES OF FORMATION OF MARKETING SUSTAINABILITY OF AN ENTERPRISE IN THE CONTEXT OF MODERN CHALLENGES - ZHEHUS, Olena; PAKHUCHA, Ellina; PETRIIANCHUK , Kateryna; SHYIAN, Denis (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article focuses on the problem of peculiarities of formation of marketing sustainability of enterprise in the context of modern challenges, as an important part of effective management, as well as an important component of strategic management decision-making.  The concepts and trends in marketing that influenced the development of strategies and approaches in the field of marketing and played a key role in shaping the concept of sustainable marketing are studied. Approaches to the interpretation of the definition of "marketing sustainability" are considered and the author's own vision of this concept is formed.  On the basis of the carried out research, the components of marketing sustainability of enterprise have been formed, which allow the enterprise to function effectively in uncertain conditions and competitive environment.  Particular attention is paid to the following components: financial and economic sustainability; production sustainability; marketing mix; staff sustainability; environmental sustainability; organisational sustainability; technological sustainability; risk management. The article considers an important component of marketing sustainability - anti-crisis sustainability, which includes measures to manage market risks and maintain market position in adverse circumstances.  The role of digital marketing in the process of forming the marketing sustainability of an agrarian enterprise is researched, which lies in its ability to adapt to modern trends and use digital tools to optimise business processes.  The features and possibilities of using Internet marketing for an agricultural enterprise are grouped. The focus is on the following tools: website and online presence; social media; blogging and video content; email; online marketplaces; online advertising; content marketing; geo-targeting and mobile marketing. Digital marketing opens up great opportunities for agribusinesses to promote products, interact with customers and expand markets.
Keywords: marketing sustainability; agricultural enterprises; sales policy; anti-crisis stability; competitiveness; digital marketing